Cyberspace Security and Defense: Research Issues Proceedings of the NATO Advanced Research Workshop on Cyberspace Security and Defense: Research Issues, Gdansk, Poland, from 6 to 9 September 2004. - Kowalik, Janusz S.; Gorski, Janusz; Sachenko, Anatoly (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry, 2005)
Cyberspace security is a critical subject of our times. On one hand the development of Internet, mobile communications, distributed computing, computer software and databases storing essential enterprise information has helped to conduct business and personal communication between individual people. On the other hand it has created many opportunities for abuse, fraud and expensive damage. This book is a selection of the best papers presented at the NATO Advanced Research Workshop dealing with the Subject of Cyberspace Security and Defense. The level of the individual contributions in the volume is advanced and suitable for senior and graduate students, researchers and technologists who wish to get some feeling of the state of the art in several sub-disciplines of Cyberspace security. Several papers provide a broad-brush description of national security issues and brief summaries of technology states. These papers can be read and appreciated by technically enlightened managers and executives who want to understand security issues and approaches to technical solutions. An important question of our times is not "Should we do something for enhancing our digital assets security", the question is "How to do it".